Assessment of carbon storage potential of existing agro-forestry systems in Bastar district, Chhattisgarh, India - Pradhan, Adikant; Jha, A; Nag, S.K; Chandrakar, T; mukherjee, S.C (Indian Journal of Agroforestry, 2022)
Plantation of trees on bund, homestead garden, block and road side plantation area age old land use phenomenon which integrates multipurpose trees with crops and livestock. These practices have great potential for offsetting of climate vagaries through stabilizing atmospheric CO2. Carbon sequestration ability of the system was studied in seven blocks (Bastar, Bakawand, Lohandiguda, Jagdalpur, Bastanar, Darbha and Tokapal) of Bastar districts Chhattisgarh, for which individual survey of each site was conducted to collect primary and allometric data of DBH, biomass, volume and related parameters on existing agro-forestry systems. Plantations have a total mean biomass of 554.9 t-C from the observation of 21 plantation sites of teak in district with standard deviation of 505.4. The overall biomass considering plantation stands, the highest biomass (4151.1 t-C) at Chinari site followed by Matnar (3384.6 t-C), Karpawand (2907.9 t-C), Rajpur (2596.9 t-C), and Kongarpal (1483.3 t-C) and lowest was in Titirgaon (17.4 t/ha) due to volume differences and among plantation sites growth differed markedly over the region. Similar trend was noticed with total carbon stocks. Soil organic carbon was ranged 0.112 to 0.913% in the upper 100 cm depth with individual agro-forestry system mustered an average of 0.692% (teak), 0.422% (Acacia) and 0.502% (eucalyptus) from surveyed areas. Hence, particular spot survey and remote sensing techniques might be successfully tool in assessing carbon sequestration potential of agro-forestry systems in a district.